1977
DOI: 10.1002/hlca.19770600334
|View full text |Cite
|
Sign up to set email alerts
|

The Photochemistry of 2‐Cyclopentenyl Methyl Ketones

Abstract: Summary2-Cyclopentenyl and 3-phenyl-2-cyclopentenyl methyl ketones (15-18, 30, 31) undergo a 1,3-acetyl shift on direct irradiation, and the oxa-di-7c-methane rearrangement to photochemically non-interconverting endo and exo bicyclo-[2.l.O]pentyl methyl ketones on triplet sensitization. Exceptions include the 2-methyl-3-phenyl-2-cyclopentenyl methyl ketone 32 and the I-phenyl-2-cyclopentenyl methyl ketone 44 which are unreactive on direct irradiation and on triplet sensitization, respectively, and the 2-phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

1977
1977
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 81 publications
2
12
0
1
Order By: Relevance
“…The problem of the nature of the excited states involved in the ODPM rearrangement has also deserved a lot of attention. The first examples reported on the photochemical reactivity of β,γ-unsaturated ketones fit a pattern in which direct irradiation yielded products resulting from 1,3-acyl migration while the triplet-sensitized irradiation brought about the formation of ODPM products. 1c-f On the basis of these results, together to CNDO-MO calculations, phosphorescence studies, ,− quenching and sensitization experiments, ,,,, the excited state responsible for the rearrangement was considered to be the alkene T 1 state. The fact that the 1,3-acyl shift was not observed on triplet-sensitized irradiation and was not quenched by triplet quenchers, , in addition to nuclear polarization effects (photo-CIDNP) 79a,b favored the assignment of a keto S 1 (n,π*) excited state for the 1,3-acyl shift reaction.…”
Section: B the Nature Of The Excited State Involved In The Odpm Rearr...mentioning
confidence: 96%
See 1 more Smart Citation
“…The problem of the nature of the excited states involved in the ODPM rearrangement has also deserved a lot of attention. The first examples reported on the photochemical reactivity of β,γ-unsaturated ketones fit a pattern in which direct irradiation yielded products resulting from 1,3-acyl migration while the triplet-sensitized irradiation brought about the formation of ODPM products. 1c-f On the basis of these results, together to CNDO-MO calculations, phosphorescence studies, ,− quenching and sensitization experiments, ,,,, the excited state responsible for the rearrangement was considered to be the alkene T 1 state. The fact that the 1,3-acyl shift was not observed on triplet-sensitized irradiation and was not quenched by triplet quenchers, , in addition to nuclear polarization effects (photo-CIDNP) 79a,b favored the assignment of a keto S 1 (n,π*) excited state for the 1,3-acyl shift reaction.…”
Section: B the Nature Of The Excited State Involved In The Odpm Rearr...mentioning
confidence: 96%
“…The acetone-sensitized irradiation of the enantiomerically pure cyclic ketone 31 gives 32 , in high chemical yield, and with 95% optical purity. , The direct irradiation of 33 brings about the formation of the endo isomer 34 in quantitative yield . A series of studies on the ODPM rearrangement of cyclopentenyl ketones 35 show that all of them yield preferentially the endo product 36 . The stereochemical results observed for the compounds collected in Scheme suggest concertedness or slow conformational equilibration of intermediates.
22
…”
Section: A the Mechanismmentioning
confidence: 99%
“…(2)); 1,24 (s, 2 H3C-C(4)); 1,67-1,84 (m, H3C-C (7)); 2,94 (qi, /=7, H-C(2)); 4,6-4,7 und 4,83-4,95 (2m, 2 H-C(8)); 5.6 (AB-System, V A = 5,41, v B = 5,80, J = 12, B-Teil durch allylische Kopplung verbreitert, H-C (5), H-C (6)). -MS.: 180 (24, M + , C12H200), 110 (19), 109 (IOO), 81 (19), 70 (64), 67 (50), 55 (18), 43 (loo), 41 (29).…”
Section: -Isopropyl-5-mefhyl-4-hexen-2-onunclassified
“…had not been taken into account, and the comparatively small effects observed at 25" had been judged mechanistically insignificant. As a consequence, the results were erroneously interpreted in favour of a concerted 1,3-acyl-shift mechanism [3]. The finding that the photoracemization of (R)-(+)-l a and the 1,3-acyl-shift in a suitably deuteriated derivative of l:a occur with equal rates…”
mentioning
confidence: 99%
“…The formation of the thermally labile [34] oxadi-n-methane-rearrangement products on direct irradiation, which remained below reliable detection limits in the first photochemical study of Ib [3], has now been demonstrated by the use of improved analytical conditions. Figure 3.…”
mentioning
confidence: 99%